The problem of emotional learning in the history of pedagogical thought (Pedagogy of Higher and Secondary Education, 2011)
The problem of an emotionality of training in the history of development of pedagogical thought is considered in this article. It is specified pedagogical essence of concept “emotionality of training”.
Keywords: emotions; feelings; emotionality of training; a principle of an emotionality of training